2008
DOI: 10.1002/adfm.200800146
|View full text |Cite
|
Sign up to set email alerts
|

A Birefringent and Transparent Electrical Conductor

Abstract: We have developed a range of thin film coatings that are transparent in the visible, electrically conducting, adjustably birefringent and capable of aligning calamitic liquid crystals. The coatings were fabricated from indium tin oxide by oblique or glancing angle deposition, and a wide range of microstructures such as helices, chevrons, uniaxial posts and biaxial slabs were produced. Under many deposition conditions, these structures showed optical transmittance and electrical conductivity comparable to stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…Because of the anisotropic column structure, the sheet resistance parallel to the deposition plane is larger than that perpendicular to the deposition plane. The similar results have been reported for oblique angle deposited ITO thin films [16]. As the flux incident angle becomes larger, more voids are introduced into the thin films.…”
Section: The Optical and Electrical Anisotropy Of Ato Thin Filmssupporting
confidence: 80%
See 1 more Smart Citation
“…Because of the anisotropic column structure, the sheet resistance parallel to the deposition plane is larger than that perpendicular to the deposition plane. The similar results have been reported for oblique angle deposited ITO thin films [16]. As the flux incident angle becomes larger, more voids are introduced into the thin films.…”
Section: The Optical and Electrical Anisotropy Of Ato Thin Filmssupporting
confidence: 80%
“…Oblique angle deposition (OAD) is a convenient method to fabricate thin films with a variety of nanostructures and unique optical properties [12][13][14][15]. Recently, transparent conductive thin film prepared by OAD technique is confirmed to improve the optical, electrical and light emitting properties of liquid crystal display (LCD) and light emitting diode (LED), which shows greatly potential application in photoelectrical field [16][17][18]. However, to our best knowledge, as one of important transparent conductive thin films, the research on ATO thin films prepared by OAD technique has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to its low resistivity ($10 À4 X cm), high transmittance in the visible range (80-90%) and low-deposition temperature, tin-doped indium oxide (ITO) is the most popular TCO used by industry [314,315]. [317], (E and F) taken from [88].…”
Section: Transparent Conductive Oxidesmentioning
confidence: 99%
“…The fabrication of highly porous and/or sculptured ITO thin films has been attempted by e-beam OAD from ITO pellets, both under high vacuum conditions [316][317][318][319][320][321][322][323][324][325][326][327] and in a carrier gas flux (usually nitrogen) [320,[328][329][330]. Fig.…”
Section: Transparent Conductive Oxidesmentioning
confidence: 99%
“…We additionally show that the polarization-dependent detection in LiNbO 3 can be utilized to reveal information about the LiNbO 3 crystal orientation and the SiO 2 /LiNbO 3 interface [6][7][8]. This approach can also be applied to characterize a variety of further complex layer systems based on e.g., birefringent polymers [9], nanocomposites [10], or indium tin oxide (ITO)-based [11] devices. In addition, newly emerging materials, e.g., nanowire-based assemblies [12,13] exhibiting strong birefringence could be interesting to study from a more fundamental research point of view.…”
Section: Introductionmentioning
confidence: 96%